2006
DOI: 10.1159/000089922
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Formulation for Bronchial Asthma: A Controlled Clinical Trial to Compare Its Efficacy with Oral Salbutamol and Theophylline

Abstract: Background: Plant-based medicine is the 3rd most popular choice of both adults (11%) and children (6%) suffering from Asthma. While several plant-based formulations have been reported for the treatment of asthma in the past, many authors have published their reservations on clinical trials carried out using complementary and alternative medicines. Objectives: The authors desired to eliminate the shortcomings of the earlier clinical trials carried out by many investigators in a structured study. Therefore, a 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
(17 reference statements)
0
16
0
Order By: Relevance
“…The remainder were RCTs using either parallel groups 14,[18][19][20][21][22][23][24][25][26][27][28][29][30] or a crossover design. [31][32][33][34][35][36][37][38][39][40] All were double blinded except one single blinded study where the colours of study and placebo medicine sachets differed.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The remainder were RCTs using either parallel groups 14,[18][19][20][21][22][23][24][25][26][27][28][29][30] or a crossover design. [31][32][33][34][35][36][37][38][39][40] All were double blinded except one single blinded study where the colours of study and placebo medicine sachets differed.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39][40] All were double blinded except one single blinded study where the colours of study and placebo medicine sachets differed. 26 Sample sizes ranged from eight 32 to 334, 13 six studies recruited children 13,14,19,23,24,35 although one of these reported subjects up to age 55 24 (clarification was sought but not received) -and one a mixed age group of 14-20 yrs. 21 Age was not stated in five studies, 17,25,27,37,38 and the remainder recruited adults.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations